Long-term response to sequential anti-HER2 therapies including trastuzumab-deruxtecan in a patient with HER2-positive metastatic breast cancer with leptomeningeal metastases: a case report and review of the literature - de Bernardi, Axel; Bachelot, Thomas; Larrouquère, Louis (Frontiers in Oncology, 2024)
The incidence of leptomeningeal metastases (LM) is increasing among breast cancer patients, but their prognosis remains dismal. Many therapeutic options are now available to treat HER2-positive (HER2+) metastatic breast cancer (MBC) involving the central nervous system (CNS). This case report illustrates a long-lasting response of more than 2 years in a patient with HER2+ MBC with LM after sequential administration of systemic and intrathecal (IT) anti-HER2 therapies and highlights that an appropriate treatment of HER2+ LM can result in durable survival.